Penerapan Prinsip Keuangan Berbasis Al-Qur’an dalam Optimalisasi Fintech Syariah di Indonesia - Gazali, Hidayatul Azizah; Fahmi, A. Syaiful; Auliya, Sefri (Universitas Islam Lamongan, 2025)
The rapid development of digital financial technology (Fintech) in Indonesia has created significant opportunities to expand financial inclusion. However, it also presents challenges in ensuring that these services align with Sharia principles. The persistent challenges faced by Sharia Fintech in Indonesia, which may hinder the smooth operation of Sharia-compliant financial services, constitute one of the urgencies of this research. Sharia Fintech, as an alternative solution, requires a more structured implementation of financial principles based on the Qur’an to provide optimal benefits while adhering to Islamic values. This study aims to analyze how the application of financial principles based on the Qur’an can optimize Sharia Fintech in Indonesia. This research is categorized as a literature study with a qualitative approach. The data analysis method applied is content analysis. The findings of this study emphasize that the Qur'an serves as the primary foundation in establishing an Islamic financial system that prioritizes transparency, accountability, and security in financial transactions. These Qur'anic principles of finance can be optimized in the practice of Islamic fintech, serving as a means to strengthen public trust. Although Islamic fintech faces several challenges, the implementation of Qur'an-based strategies can be the key to fostering the optimal development of Islamic fintech in Indonesia.